The ResD Response Regulator, through Functional Interaction with NsrR and Fur, Plays Three Distinct Roles in Bacillus subtilis Transcriptional Control - Henares, Bernadette; Kommineni, S.; Chumsakul, O.; Ogasawara, N.; Ishikawa, S.; Nakano, M. (American Society for Microbiology, 2014)
The ResD response regulator activates transcription of diverse genes in Bacillus subtilis in response to oxygen limitation. ResD regulon genes that are the most highly induced during nitrate respiration include the nitrite reductase operon (nasDEF) and the flavohemoglobin gene (hmp), whose products function in nitric oxide (NO) metabolism. Transcription of these genes is also under the negative control of the NO-sensitive NsrR repressor. Recent studies showed that the NsrR regulon contains genes with no apparent relevance to NO metabolism and that the ResD response regulator and NsrR coordinately regulate transcription. To determine whether these genes are direct targets of NsrR and ResD, we used chromatin affinity precipitation coupled with tiling chip (ChAP-chip) and ChAP followed by quantitative PCR (ChAP-qPCR) analyses. The study showed that ResD and NsrR directly control transcription of the ykuNOP operon in the Fur regulon. ResD functions as an activator at the nasD and hmp promoters, whereas it functions at the ykuN promoter as an antirepressor of Fur and a corepressor for NsrR. This mechanism likely participates in fine-tuning of transcript levels in response to different sources of stress, such as oxygen limitation, iron limitation, and exposure to NO.